Performance, heterosis and heritability in selected tropical maize single, double and three-way cross hybrids - Saleh, G.B.; Abdullah, D.; Anuar, A.R. (Cambridge University Press, 2002)
A series of tropical maize hybrids, involving 10 single, four double and four three-way crosses were evaluated with their parental inbred lines and three control varieties, at Universiti Putra Malaysia, Serdang, Malaysia, in a randomized complete block design, with three replications. The objectives were to identify hybrids superior for yield, yield components and other agronomic traits, to estimate heterosis revealed by the hybrids, and to estimate broad-sense heritability for important characters in the populations. The hybrids were found to vary highly for grain yield and most other traits measured. High estimates of heterosis were shown by grain yield, ear weight and grain weight per ear, moderate for plant and ear heights, shelling percentage, ear diameter, number of kernel rows per ear, number of kernels per ear row and 100-grain weight. The hybrids flowered and matured earlier than their respective inbred parents. Estimates of broad-sense heritability also varied with characters. Moderate heritability was shown for grain yield indicating a substantial amount of genetic variation in this population of hybrids. Low and negligible heritability for days to silking and 100-grain weight indicate that these traits were very much influenced by environmental factors. Based on the overall performance of the hybrids, the single cross, SC-2, the double cross, DC-11 and the three-way cross, TWC-15, were found to have high potential. No obvious differences were observed in performance among the three categories of hybrids, the single, double and three-way crosses.